The Effects of Increasing Annealing Temperature on Some Physical Properties of a Glass/GaN/InGaN Film produced with TVA - Erdoğan, Erman (My University, 2020)
In this study, GaN/InGaN semiconductor films were deposited on glass substrate using thermionic vacuum arc(TVA) method. In order to improve some physical properties of the produced films, thermal annealing wasperformed at different temperatures and the effect of annealing temperature on the optical and surfaceproperties of the films was investigated. Transmittance and absorption spectra were taken using a UV-VISspectrophotometer and optical band gap energies were determined. The surface images and surface roughnessvalues of the films were obtained using atomic force microscopy (AFM). According to the results obtained,some physical properties of GaN/InGaN films were improved by thermal annealing and these films wereinvestigated for use in various technological fields.